Full mouth rehabilitation of hypomaturation type amelogenesis imperfecta: A clinical report - Sushil K. Kar; Arvind Tripathi; Saumyendra V. Singh (Journal of Oral Biology and Craniofacial Research, 2012)
Problem considered: This clinical report describes the prosthodontic treatment of an 18-year-old female diagnosed with amelogenesis imperfecta. Materials and method: The specific objectives of the treatment were to restore esthetics and masticatory function. Metal-ceramic fixed partial dentures were fabricated at the existing vertical dimension of occlusion utilizing the PMS occlusal scheme. Results: Clinical examination of the patient 12 months after treatment revealed no evidence of disease or degeneration of the restored teeth. Conclusion: The patient's esthetic and functional expectations were satisfied.